Preparasi Katalis CaO/Fly Ash Dan Penggunaannya Pada Reaksi Transesterifikasi Minyak Sawit Off-Grade Menjadi Biodiesel - Robi Maulana; Zuchra Helwani; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
A palm fly ash supported calcium oxide (CaO) catalyst was prepared and used in transesterification from off-grade palm oil for biodiesel production. The catalyst synthesized by loading CaO of calcium nitrate tetrahydrate (Ca(NO3)2.4H2O) into fly ash through impregnation method. The optimum catalyst preparation conditions were determined by influence of calcination temperature and weight ratio of Ca(NO3)2.4H2O and fly ash. Catalyst with highest catalytic activity was achieved when calcined at 800 oC and proportion of Ca(NO3)2.4H2O to fly ash is 80:20. Under the conditions of oil : methanol ratio of 1:6, catalyst dosage of 6 wt% and temperature of 70 oC for 2 h, the biodiesel yield reaches to 71,77%. CaO, SiO2, Ca(OH)2 and Ca2SiO4 were found in the catalyst through X-ray diffraction (XRD) while the basic strength of the catalyst H_ > 9,3 was determined by using Hammett indicator phenolphthalein. Surface area of the developed catalyst is 24,342 m2/g through Brunauer-Emmett-Teller (BET). Characteristics of biodiesel such as density, kinematic viscosity, acid value, flash point has been matched with standard for biodiesel specification of Indonesia.Keywords: calcium oxyde, catalyst, fly ash, biodiesel, off-grade palm oil, impregnation,calcination, transesterification.